COMPARISON OF THE ACCURACY OF PERIAPICAL RADIOGRAPHY AND CONE-BEAM COMPUTED TOMOGRAPHY IN THE DIAGNOSIS OF INFLAMMATORY ROOT RESORPTION (CIPEEX, 2025)
The objective of this study was to compare the accuracy of periapical radiography and cone-beam computed tomography (CBCT) in detecting inflammatory root resorption. Fourteen patients referred to the Emergency Service of the School of Dentistry of the Federal University of Goiás were evaluated. The sample consisted of 52 teeth and was divided according to tooth group: 6 anterior, 23 premolars, and 23 molars, with 88 roots analyzed. Periapical abscess without fistula stage I was diagnosed in 1 tooth (1.92%), pulp necrosis in 1 tooth (1.92%), asymptomatic apical periodontitis in 36 teeth (69.23%), and symptomatic apical periodontitis in 14 teeth (26.92%). Regarding the type of infection, 42 teeth (80.77%) presented primary infection and 10 teeth (19.23%) secondary infection. A high prevalence was observed after the use of CBCT. However, no statistically significant difference was found between periapical radiography and CBCT. Advances in clinical evaluation have greatly improved diagnostic accuracy. CBCT provides a greater probability of correct management of resorption lesions compared to intraoral radiographs.
Keywords: Inflammatory root resorption; CBCT; Periapical radiography